The Simplest Modified Vacuum Assisted Closure to Treat Chronic Wound : Serial Case Report - Mahandaru, Danu; Seswandhana, Rosadi (Lingkar Studi Bedah Plastik Foundation, 2012)
Among the current adjunctive treatment modalities available for the treatment of chronic wounds, vacuum-assisted closure therapy showed promising results. However, the VAC Therapy system is expensive, requires extensive amounts of product and needs a power source at all times. In this article, the authors introduce and review their experience with simplest modified vacuum assisted closure (smVAC) for treatment of chronic wound. Three patients with chronic wound came to the plastic surgery division at Sardjito hospital in early 2010 and were treated using simplest modified vacuum assisted closure (smVAC). After the wound bed was ready, split thickness skin graft (STSG) were performed to close the wound and smVAC was used to assist the graft placement. All patients underwent successful healing and reported satisfaction with their results. There were no side effects from using this device, such as maceration, necrosis and bleeding. Through the serial cases, the smVAC had shown to serve its function in providing adequate vacuum pressure for wounds. It is an alternative to the original vacuum assisted closure.